2018
DOI: 10.1159/000489752
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Computer Tomography Assessment of the Effect of Angiotensin II On Blood Flow Distribution in Rabbits with Intrarenal VX2 Tumors

Abstract: Background/Aims: Unlike other organs, which only have one set of capillary network, the renal microvasculature consists of two sets of capillary network series connected by efferent arterioles. Angiotensin II constricts the efferent glomerular artery. Hence, renal tumor blood flow (BF) distribution may be different from tumors in other organs. This study aims to investigate the effects of angiotensin II on the hemodynamics of intrarenal VX2 tumors using perfusion computed tomography(CT). Methods: Twenty-four m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Studies have shown that human renal cell carcinoma also has EPR effect. 6 , 7 The in vitro tumor perfusion model we constructed effectively avoids the influence of immune clearance and other factors in blood circulation, creates conditions for the study of human EPR effect, and also provides more reliable theoretical basis for the design and improvement of nano drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that human renal cell carcinoma also has EPR effect. 6 , 7 The in vitro tumor perfusion model we constructed effectively avoids the influence of immune clearance and other factors in blood circulation, creates conditions for the study of human EPR effect, and also provides more reliable theoretical basis for the design and improvement of nano drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 30 rabbits were randomly divided into three groups to establish a paraspinal intramuscular dual tumor model. Referring to previous studies, we included ten rabbits in each group (SM, S & LN, 2021;Xu et al, 2018). The tumor source for inoculation used in each group were different.…”
Section: Ct-guided Implantation Of Vx-2 Tumorsmentioning
confidence: 99%